Perkembangan morfologi kawasan Kota Lama Kupang - Lamahoda, Rudini A. R. B.; Setiadi, Amos; Lake, Reginaldo Christophori; Samara, Ricky (EMARA: Indonesian Journal of Architecture, 2020)
Kupang is the capital of East Nusa Tenggara Province, located on the coast of Kupang Bay, northwest of Timor Island. The development of Kupang old city area began in the 15th century, starting as a city initiated by King Helong until the Dutch, Portuguese, and Chinese governments' intervention. It has a unique morphology of the city area to research. The purpose of this study is to identify the development of the Kupang Old City area over several periods and analyze any changes and comparisons related to the morphology of the Kupang Old City area. Exploratory, descriptive research with tissue analysis method is used in this study to read the history that occurred in Kupang old city area from the early period formed the 15th-century area until the 21st century.Furthermore, the historical reading method wasused to find changes and morphological comparisons of the Kupang Old City area from the 15th to the 21st century and explain how Kupang old city spaces began to grow and develop. This research concluded that the Kupang old city area began to develop because it has the foremost generator that is the entry of King Helong's power to make Kupang Old City a city on Timor Island. The findings of changes and comparisons of the morphological development of Kupang Old City area are due to the influx of Dutch, Portuguese, and ethnic Chinese,and there is a change after Indonesia's independence, namely the change in the status of Kupang old city area based on the evolving political aspects